New Tetramic Acids Comprising of Decalin and Pyridones From Chaetomium olivaceum SD-80A With Antimicrobial Activity - Wang, Xinzhu; Zhao, Liya; Liu, Chao; Qi, Jun; Zhao, Peipei; Liu, Zhaoming; Li, Chunlei; Hu, Yingying; Yin, Xin; Liu, Xin; Liao, Zhixin; Zhang, Lixin; et al. (Frontiers in Microbiology, 2020)
Cycloaddition reactions such as intramolecular Diels-Alder (IMDA) are extremely important in constructing multicyclic scaffolds with diverse bioactivities. Using MycB as a biomarker, three new polyketides—Chaetolivacines A (1), B (3) and C (4) —with one known compound Myceliothermophin E (2) comprising of decalin and 4-hydroxy-2-pyridones were obtained from the culture of Chaetomium olivaceum SD-80A under the guidance of gene mining. The structures of these compounds were established using detailed 1D, 2D NMR and HRESIMS analysis. The relative and absolute configurations of the compounds 1, 3 and 4 were elucidated by NOESY and ECD. The biosynthesis pathways of these compounds were proposed, which involves in three key genes ChaA (PKS-NRPS), ChaB and ChaC. Compounds 1–4 were tested for their antimicrobial activities, and compounds 2 and 3 showed moderate bioactivity against Staphylococcus aureus (SA) and methicillin-resistant Staphylococcus aureus (MRSA) with MIC values of 15.8 and 27.1 μM. The results showed that configuration of C-21 in 3 and 4 is important for anti-SA and anti-MRSA activities. This study reveals the significant potential of the genus Chaetomium in producing new polyketide synthase-nonribosomal peptide synthetases (PKS-NRPS), therefore increasing the speed in the mining for new sources of antimicrobial agents.